Plagiarism in undergraduate and graduate: Narrative Review (Revista de Medicina Clinica, 2020)
Academic integrity is a value that needs to be cultivated from teaching activities to transmit it to undergraduate and graduate students. It is important to make it aware that the academic, legal and ethical dilemmas that emanate from plagiarism, whether intentional or inadvertent, have great repercussions.In this narrative review we address aspects to consider to avoid getting involved in plagiarism at least inadvertently, because, if you intend to do so, any advice will not prevent you from incurring
Keywords: Keywords: Plagiarism; Undergraduate Education in Medicine; Medical specialties; Education